Quarter-life millennials’ perspectives on women’s role and career in industry 4.0 - Silaban, Tio Gabriel Laspahot; Pratama, Andika Putra (Journal of Business and Management, 2020)
Abstract. Womens’s empowerment now has become one of the most important concerns of the 21st century. Women take a dual role in their lives, domestic and public. Many women have held top leadership in an institution, such as ministers or managers of companies. The emergence of the industrial revolution 4.0 must be used properly handled by women as an opportunity for women as part of promising world society. The fact that women are still called to work in the industrial world still has several challenges. Many educated women are also less likely than men to seek careers in various industries. This study reveals that students from various colleges in Indonesia as part of the millennial generation who enter or are living in a quarter-life cycle, have diverse perspectives on the role and career of women in the industry 4.0. It was found that there are many factors and aspects that underlie their diverse perspectives and are influenced by students' insights and experiences. This study concludes that the complexity experienced when dealing with millennials impacts on the formation of millennial generation perspectives on the role and career of women in industry 4.0.Keywords: Millennials, Women’s Role, Women’s Career, Industrial Revolution 4.0, Quarter-Life